2021
DOI: 10.1002/pmrj.12562
|View full text |Cite
|
Sign up to set email alerts
|

Keep Your Move in the Tube” safely increases discharge home following cardiac surgery

Abstract: Background: Restrictive sternal precautions intended to prevent cardiac surgery patients from damaging healing sternotomies lack supporting evidence and may decrease independence and increase postacute care utilization. Data regarding the impact of alternative approaches on safety and outcomes are needed to guide evidence-based best practices. Objective: To examine whether an approach allowing greater freedom during activities of daily living than permitted under commonly used restrictive sternal precautions c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 14 publications
2
20
0
1
Order By: Relevance
“…For specific activities, MIT patients were more independent with bed mobility skills and transfers on admission to rehabilitation. Gach (2021) also found that patients on MIT precautions had greater functional mobility on discharge from acute care hospital. 15 Because standard sternal precautions prohibit patients from bending and reaching, patients on these precautions cannot participate in lower-body dressing without first learning how to use adaptive equipment.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…For specific activities, MIT patients were more independent with bed mobility skills and transfers on admission to rehabilitation. Gach (2021) also found that patients on MIT precautions had greater functional mobility on discharge from acute care hospital. 15 Because standard sternal precautions prohibit patients from bending and reaching, patients on these precautions cannot participate in lower-body dressing without first learning how to use adaptive equipment.…”
Section: Discussionmentioning
confidence: 85%
“…In agreement with other reports, patients adhering to MIT did not experience more sternal disruptions. 7–15 This provides additional evidence that patients adhering to MIT are not at greater risk of sternal disruptions, even within the IRF.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations